Teachers’ Folk Pedagogies - Ilić, Marina Ž.; Bojović, Žana P.; Sudzilovski, Danijela M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In the last few decades, a large portion of scientific literature has been dedicated to the questions of realization of teaching and its improvement. However, one question remains in the background – folk pedagogies and their influence on teaching.The main objective of this paper is to help us get acquainted with this phenomenon that exists in the teaching practice, its significance and pedagogical implications. In the first part of the paper, we deal with definitions of folk pedagogies and related concepts and their mutual relationship, in order to analyze the similarities and differences in the meaning of the concepts in use. Starting from important determinants of teachers’ folk pedagogies, we will attempt to reassess some of the proposed methods and ways to raise consciousness about teachers’ folk pedagogies, methods to analyze and change them. Based on the existing knowledge on teachers’ folk pedagogies, we will try to point out their significance and implications they have on education practice. Starting from the existing findings about folk pedagogies, we have separated three important implications for educational practice: a) teachers should be viewed as creators of their own coherent theories about learning and teaching; b) changing and improving one’s teaching practice is a result of the teacher’s willingness to reflect on his or her own folk pedagogies; and c) teachers’ folk pedagogies should be seen as the starting point for teacher professional development programs.